The devil's arithmetic - Yolen, Jane. (New York, N.Y., U.S.A. : Puffin Books, 1990)
Hannah resents the traditions of her Jewish heritage until time travel places her in the middle of a small Jewish village in Nazi-occupied Poland.
"Ages 12 up"--Jkt.
Keywords: Jews -- Fiction; Concentration camps -- Fiction; Time travel -- Fiction